Chemical and Structural Properties of Jordanian Diatomaceous Clay Supported Metal Oxides - M. Musleh, Salem (Asian Journal of Chemistry, 2016)
Metal oxides of titanium and vanadium were deposited on the native Jordanian diatomaceous clay. The chemical and structural properties of the prepared samples were investigated using XRF, ICP, XRD and FTIR techniques. The diatomaceous clay supported metal oxides were used in preliminary experiments to explore their interaction with aqueous phenol solution under thermal and photochemical conditions, in the presence and absence of hydrogen peroxide. The results showed that the metal oxides have interacted with diatomaceous clay and caused some structural changes. These were reflected in the surface area of the samples and their activity in the phenol reactions.